Translation, Adaptation, and Psychometric Validation of the Indonesia Version of Job Diagnostic Survey: Hospital Nurse Setting - Yupin Aungsuroch; Mary L. Fisher; I Gede Juanamasta; Ni Made Nopita Wati; R. Tri Rahyuning Lestari (Jurnal Keperawatan Soedirman, 2024)
A job diagnostic survey is used to measure work or job characteristics. However, there is limited study exploring the psychometric properties of the Indonesian version. This study aimed to validate the Indonesian version of the Hack and Oldham Job Diagnostic Survey.